2020
DOI: 10.3991/ijet.v15i23.19029
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Technology-Based Improvement of Teaching Ability of Professional Courses in Art Design

Abstract: Despite the development of intelligent technology, there are many problems in the improvement of teaching ability of professional courses in art design, namely, the impact from multiple factors, the imperfectness of the evaluation index system, and the lack of quantitative analysis. To solve the problems, this paper probes deep into the connotations and influencing factors of the teaching ability of the said courses in the context of intelligent technology. Through theoretical analysis, several strategies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Therefore, provided that the instructors applied an integration of the learning patterns of active learning and childcentered learning, this would fully generate the perfection to level up the knowledge and craft skills for the learners, including create interest with high effectiveness. Finally, according to the results for the student groups, this confirmed that the ideas had an increasing trend of generating better scores with the students after applying these two learning patterns simultaneously; the better result from the learners showed the additional skills [44]; such as, good thinking skill and flexible thinking skill after graduation from the classrooms [45][46].…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, provided that the instructors applied an integration of the learning patterns of active learning and childcentered learning, this would fully generate the perfection to level up the knowledge and craft skills for the learners, including create interest with high effectiveness. Finally, according to the results for the student groups, this confirmed that the ideas had an increasing trend of generating better scores with the students after applying these two learning patterns simultaneously; the better result from the learners showed the additional skills [44]; such as, good thinking skill and flexible thinking skill after graduation from the classrooms [45][46].…”
Section: Discussionmentioning
confidence: 73%
“…Timely feedback is needed to improve learning and optimize teaching and learning. e smart classroom visualizes data with the support of data analysis technology, and teachers and students can receive timely learning data [17]. As a result, they can visually grasp the learning situation, thus facilitating the improvement of teaching and learning and the achievement of teaching goals.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of online technology and information technology has brought certain changes to the learning environment, learning contents, and learning methods in the field of education [1][2][3][4][5][6]. Hybrid learning, which is in line with the national strategy of information-based education, can promote the autonomous learning ability, cooperative learning ability, and personalized development of students [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%